Regional and central hemodynamics in ischemic optic neuropathy (Ukrainian Journal of Ophthalmology, 2026)
Background: As ocular vascular disorders are a major cause of visual loss and affect working-age individuals, they are of particular social importance.Purpose: To investigate visual functions and ocular hemodynamics in ischemic optic neuropathy (ION) in the presence of changes in systemic and regional hemodynamics.Materials and Methods: Forty persons with ION underwent examination and treatment. Of these, 9 and 31 subjects had unilateral and bilateral ION, respectively.Patients underwent assessment of visual acuity, ophthalmoscopy, biomicroscopy, perimetry, intraocular pressure (IOP) and systemic blood pressure measurements, examination of the electrical sensitivity of the optic nerve and critical frequency of phosphene disappearance, ophthalmic rheography (ORG) and rheoencephalography (REG).Results: The data obtained indicate that there are correlations between regional blood flow characteristics and central hemodynamics parameters. This demonstrates once again that ION results from numerous etiologies, including systemic hemocirculation disorders, which agrees with the literature.In patients with low ocular pulse blood filling (OPBF), the mean pulse blood filling value for the internal carotid and vertebral-basilar systems was 71.4% lower (p < 0.05) than that in patients with normal  OPBF. In ION, ocular hemodynamics insufficiency developed in the presence of increased diastolic pressure and reduced functional adaptive capabilities of the body.Conclusion: First, in the affected eye of patients with unilateral ION, the OPBF (expressed by the RQ index) was 44.4% lower, the vascular tone in small vessels was 17% increased (p < 0.05), and the ocular blood flow velocity was 39% decreased (p < 0.05) compared to those in the fellow eye. In patients with bilateral chronic ION, the RQ, the vascular tone of vessels of any size and ocular blood flow velocities were not significantly different from those from the affected eye of patients with unilateral ION. Second, in ION, best-corrected visual acuity (BCVA) was positively correlated with RQ (r = 0.31). If the RQ was lower than in age-matched normals, the BCVA was decreased to 0.5±0.06. Third, in patients with low OPBF, the mean pulse blood filling value for all brain artery systems was 71.4% lower (p < 0.05) than in those with normal  OPBF. Fourth, in patients with low OPBF (i.e., OPBF lower than in age-matched normal controls), the mean diastolic blood pressure was 84.2±1.3 mmHg, which was 7.4% higher than those with normal OPBF (p < 0.05). Finally, adaptation potential characterizes the functional state  of central regulation of the circulation system, and its value ranged from 2.1 units to 3.2 units and from 3.2 units to 4.3 units in 58.1% and 38.7%, respectively, of patients with ION, which evidences that adaptation mechanisms were subjected to some stress or functional reserves of circulation regulation were substantially depleted, respectively.
Keywords: ischemic optic neuropathy; rheo-ophthalmogram; rheoencephalogram